Management of Malpractice Cases Against Patients in Government and Private Hospitals - Rendita Dwibarto; Fikri Rahman; Risdiarto (Citra Delima Scientific journal of Citra Internasional Institute, 2026)
Medical malpractice cases are currently a hot topic among the public because they have caused many patients to die. There have been several cases of malpractice in 2024 and 2025 at hospitals in Pangkalpinang City (both public and private hospitals). In the context of healthcare, supervision plays a very important role. To resolve these issues, an appropriate communication strategy is needed to generate a positive reciprocal effect. Unwanted news reported by the media can have a negative effect on hospitals. Therefore, hospitals must immediately handle such cases using issue management. In the above case, the hospital's public relations department is responsible for researching issues that arise in the community, as negative news coverage has the potential to become a negative issue and harm the company. One theory that public relations can apply in handling malpractice issues is the image repair theory. Objective To implement a strategy for managing malpractice cases involving patients at hospitals in Pangkalpinang City (government and private hospitals). The method used for this study was a qualitative case study. The results of this study are the implementation of malpractice issue management strategies in hospitals. The strategies implemented in government hospitals based on Chase and Jones' theory have not been fully successful in terms of program implementation and issue evaluation. Meanwhile, in private hospitals, the implementation of malpractice issue management strategies has been carried out in accordance with hospital policies. However, the strategy cannot be said to be successful, because private hospitals have never experienced malpractice incidents.